The 'Lands of the Normans' in England (1204-1244) - University of Sheffield - Humanities Research Institute (2007)
"The "Lands of the Normans" in England (1204-44) was a one-year project, funded by the Arts and Humanities Research Council under their Route for Speculative Research. The project was based at the Department of History, University of Sheffield and housed in the university's Humanities Research Institute. The project ran from 1 October 2006 to 30 September 2007 under the direction of Professor Daniel Power. The dual aims of the project were to assess the historical consequences of the end of the Anglo-Norman realm, for England and for France, and to investigate the potential for Information Technology to contribute to historical study." [self-description]